Analisis kemampuan guru dalam menggunakan alat peraga matematika di SMP Negeri 5 Langsa - Cut Intan Salasiyah; Muhammad Zaki (Math Didactic: Jurnal Pendidikan Matematika, 2018)
The purpose of this study was to determine the ability of teachers to use teaching aids in SMP Negeri 5 Langsa. The source of the data in this study were mathematics teachers at SMP Negeri 5 Langsa and teaching aids. Data sources are explored using interview techniques and observation of teacher activities related to the use of teaching aids that are integrated in learning. This research is a descriptive study with a qualitative approach. Based on data analysis obtained information that the ability of teachers to use teaching aids is not optimal. Analysis of interviews and observations obtained information on teacher activities related to the use of mathematics teaching aids do not arrive at the concepts or mathematical formulas learned.